Neurodevelopmental Outcomes following Preterm Birth and the Association with Postmenstrual Age at Discharge - Kellner, Polly; Kwon, Jenny; Smith, Joan; Pineda, Roberta (American Journal of Perinatology, 2022)
Objective This study aimed to (1) define the prevalence of motor, cognitive, and language delays in preterm infants born <32 weeks estimated gestational age (EGA); and (2) identify the relationship between the timing of discharge from the neonatal intensive care unit (NICU) and neurodevelopmental outcome in early childhood.Study Design This retrospective study of 172 preterm infants born <32 weeks EGA and hospitalized in a level-IV NICU captured medical factors, including timing of discharge, from the NICU stay. Standardized developmental testing at 1 to 2 years corrected age was conducted in the newborn follow-up clinic.Results At 1 to 2 years corrected age, the sample had an average Bayley Scales of Infant and Toddler Development (Bayley-III) cognitive composite score of 91.5 ± 17.4, language composite score of 84.5 ± 17.3, and motor composite score of 88.9 ± 18.4. Lower EGA at birth, necrotizing enterocolitis, patent ductus arteriosus, and oxygen requirement for >28 days were independently associated with higher postmenstrual age (PMA) at NICU discharge. Higher PMA at discharge was associated with poorer cognitive outcome [p < 0.001, β = −1.1 (−1.6, −0.7)], poorer language outcome [p = 0.049, β = −0.5 (−0.9, −0.003)], and poorer motor outcome [p <0.001, β = −1.0 (−1.5, −0.5)]. For every additional week of hospitalization, scores were an average of 1.1 points lower in cognitive, 1.0 point lower in motor, and 0.5 points lower in language domains of the Bayley-III assessment.Conclusion Poorer cognitive, language, and motor outcomes were associated with longer hospitalization, even after controlling for medical risk factors known to be associated with poorer outcome. This provides further evidence for the potential role of the environment in impacting developmental outcomes of infants hospitalized in the NICU.Key Points
Keywords: hospitalization; neonatal intensive care unit; length of stay; postmenstrual age; outcomes; child development; risk factors; environment